2024
DOI: 10.5812/ans-144828
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical Manifestations of COVID-19 in Multiple Sclerosis Patients: Unraveling the Clinical Nexus

Amir Aboofazeli,
Mozhgan Mondeali,
Roxana Tajdini
et al.

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is a virus in the coronaviridae, has caused a global pandemic with various symptoms and complications. Among the groups affected by this virus are individuals with multiple sclerosis (MS), a chronic autoimmune disorder that affects the primary central nervous system (CNS). Understanding coronavirus disease 2019’s (COVID-19) impact on MS patients is crucial for optimizing patient management and developing targeted therapies due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Meanwhile, the COVID-19 pandemic underscores the urgency of infectious disease management and robust public health strategies (2). Consistent with the findings of prior research (12,13), our study also confirmed a higher prevalence of neurological symptoms, specifically headaches, dizziness, and fever.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the COVID-19 pandemic underscores the urgency of infectious disease management and robust public health strategies (2). Consistent with the findings of prior research (12,13), our study also confirmed a higher prevalence of neurological symptoms, specifically headaches, dizziness, and fever.…”
Section: Discussionsupporting
confidence: 92%